The impact of customer satisfaction on repurchase intention in e-commerce: a study in indonesia - Afinia, Shevila (Jurnal Mantik, 2024)
The rapid growth of e-commerce in Indonesia has transformed the digital economy landscape, becoming a key driver of economic development. This study aims to investigate the relationship between customer satisfaction and repurchase intention in the context of e-commerce in Indonesia. Specifically, the research focuses on understanding how customer satisfaction impacts the likelihood of customers to repurchase products or services from online platforms. The research employs a quantitative approach, utilizing a sample of 90 respondents in Semarang, Indonesia, selected through purposive sampling. Data collection is conducted through structured questionnaires, with Likert scales used to assess customer responses. Statistical analysis, including validity testing and multiple linear regression, is performed using SPSS software to examine the relationship between customer satisfaction, trust, electronic word-of-mouth, and repurchase intention. The results indicate a significant and positive relationship between customer satisfaction and repurchase intention in e-commerce. Statistical tests reveal that both customer satisfaction and trust have a significant impact on repurchase intention, with p-values of 0.023 and 0.019, respectively. In conclusion, the findings highlight the importance of prioritizing customer satisfaction in e-commerce operations to enhance customer loyalty and drive repeat purchases. E-commerce platforms in Indonesia should focus on building trust, delivering quality service, and fostering positive customer experiences to increase repurchase intention and sustain long-term success in the competitive market